Cell fusion enhances energy metabolism of mesenchymal tumor hybrid cells to sustain their proliferation and invasion - Brito, Ariadna; Merle, Candice; Lagarde, Pauline; Faustin, Benjamin; Devin, Anne; Lartigue, Lydia; Chibon, Frederic (BMC cancer, 2021)
Background Cell-to-cell fusion is emerging as a key element of the metastatic process in various cancer types. We recently showed that hybrids made from the spontaneous merging of pre-malignant (IMR90 E6E7, i.e. E6E7) and malignant (IMR90 E6E7 RST, i.e. RST) mesenchymal cells recapitulate the main features of human undifferentiated pleomorphic sarcoma (UPS), with a highly rearranged genome and increased spreading capacities. To better characterize the intrinsic properties of these hybrids, we investigated here their metabolic energy profile compared to their parents. Results Our results unveiled that hybrids harbored a Warburg-like metabolism, like their RST counterparts. However, hybrids displayed a much greater metabolic activity, enhancing glycolysis to proliferate. Interestingly, modifying the metabolic environmental conditions through the use of 5-aminoimidazole-4-carbox-amide-1-β-D-ribofuranoside (AICAR), an activator of the 5′-adenosine monophosphate (AMP)-activated protein kinase (AMPK), specifically reduced the growth of hybrids, and also abrogated the invasive capacity of hybrids displaying enhanced glycolysis. Furthermore, AICAR efficiently blocked the tumoral features related to the aggressiveness of human UPS cell lines. Conclusion Altogether, our findings strongly suggest that hybrids rely on higher energy flux to proliferate and that a drug altering this metabolic equilibrium could impair their survival and be potentially considered as a novel therapeutic strategy.